A Dress jacket (a Circassian coat). On the question of ethnographic research of the North Caucasian Cossack clothes - Luiza Sergeevna Tsareva (Вестник Майкопского государственного технологического университета, 2023)
Features of the North Caucasian Cossack uniform are currently of great interest to researchers, as it is an integral part of military life. In the first half of the XIX century the uniform of the Russian troops and Cossack regiments on the Caucasian Line was badly adapted to the local climate and geographical conditions. Officers combined items of their uniforms with the elements of a mountain suit, which created the ground for the reform of the army uniform; the same was observed in the Caucasian Cossack linear regiments, where the process of outfit unification was going on “according to the Circassian model”. The form of the Circassian model in the CLFCH was enshrined in the legislation on January 16, 1831; in 1840 - in ChCK. In the KKV formed on November 19, 1860, it was supposed to have two upper shoulder uniforms - a dress jacket (ceremonial half-caftan (robe)) of dark blue cloth and a Circassian coat of the same cut with a uniform. What, nevertheless, is the difference between the uniform (Circassian) and the Circassian robe? The preliminary work allowed us to conclude that the unifying element of the objects under the general name “Circassian” (a uniform, in particular, a Circassian robe) was only the presence of cartridge belt and V-shaped cut; the outfit of the North Caucasian Cossacks changed according to the regulations of the War Department, and its constructive and technological solution, in our opinion, was built in accordance with the constructive and technological features of the general army uniform.